ANALISIS PERBANDINGAN KINERJA EKONOMI KABUPATEN BUTON UTARA DENGAN KABUPATEN INDUKNYA - Ariani, Wa Ode Rachmasari; Lapau, Fitri (AT TARIIZ : Jurnal Ekonomi dan Bisnis Islam, 2025)
Buton Utara Regency has been a new autonomous region since 2007 as a result of the division of Muna Regency. The local government has implemented various development programs to improve its economic performance after the division. The objective of this study is to assess the economic performance of Buton Utara Regency as a new autonomous region. The data analysis method used is quantitative descriptive with an observation period from 2010 to 2023. The research findings indicate that the economic performance of Buton Utara Regency is better than that of Muna Regency in several indicators, namely economic growth, per capita GDP, and human development index (HDI) growth. However, regarding HDI values, the poverty depth index and poverty severity index show that Buton Utara Regency’s performance is lower than that of Muna Regency. Key findings indicate that fluctuations in economic growth and HDI performance categorized as moderate reflect challenges in economic stability. Policy implications emphasize the need for strengthening priority sectors and effective poverty alleviation programs based on data. The limitations of the study lie in the less in-depth analytical approach, which has not yet captured the complexity of the interplay between variables.